Perancangan Sistem Informasi Kehadiran Dosen Mengajar pada Universitas XYZ - Arif Yulianto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
XYZ university has several faculties and departments of the various fields of science. During this level of attendance, punctuality long process of teaching and teaching faculty and instructional materials delivered lecturer in class can not be monitored by the Academic Unit. Systems in use today are still using manual systems, ie lecturers who will teach or have finished teaching signed form in the presence of academic administration. So that part is hard oversee Academic lectures. That requires a computerized system that can monitor the presence and the material presented. Teaching faculty attendance information system created using Microsoft Visual Basic 2008 and SQL Server 2005. Stages of making systems require design with prototyping and design methods of data base system with the concept of context diagram, DFD (Data Flow Diagram), flowchart and ERD (Entity Relationship Diagram) . This system can be used in multiuser by utilizing technology and network infrastructure tersedia.Sistim is designed to facilitate monitoring of the presence of lecturers as well as facilitate the teaching of Administration calculate fees. Teaching materials that must be entered each end of the lecture helping the academic field to see the harmony between the lines of the Teaching Process (GBPP) the material submitted by the lecturer at every opportunity to teach. It is expected the learning process more transparent and facilitate the evaluation of the teaching process.